(untitled) (Zoological Archives: An International Journal, 2026)
Community phylogenetics – the analysis of the evolutionary relationships among co-occurring species to infer the ecological and evolutionary processes structuring communities – has emerged as a powerful framework for understanding tropical forest biodiversity, yet its application has been largely restricted to plants and birds, leaving the phylogenetic structure of tropical vertebrate communities undercharacterised. This study quantified phylogenetic community structure metrics (NRI, NTI, PD, MPD, MNTD) for vertebrate assemblages (mammals: 84 species; birds: 124 species; reptiles: 48 species; amphibians: 28 species) across 42 intact and degraded tropical forest plots in Borneo, the Congo Basin, and the Amazon (2,840 species-site records; 2020-2024), using a time-calibrated vertebrate supertree. Intact forest plots showed phylogenetic overdispersion (NRI < -1.0 in 72.4% of plots; mean MPD significantly greater than null expectation; p < 0.001) in birds and mammals, consistent with competition-driven character displacement among closely related co-occurring species. Degraded forest plots (> 50% canopy loss) showed phylogenetic clustering (NRI > +1.0 in 68.4% of degraded plots; p < 0.001), consistent with environmental filtering selecting for disturbance-tolerant lineages. Amphibians showed phylogenetic clustering in both intact and degraded plots (NRI > +1.0 in 64.4% of plots overall), suggesting habitat filtering dominates amphibian community assembly regardless of degradation state. A Phylogenetic Degradation Index (PDI) – the shift in NRI from negative to positive values along the intact-degraded gradient – predicted total vertebrate abundance loss with r = -0.74 and species richness loss with r = -0.68 (both p < 0.001), confirming that shifts in phylogenetic structure reflect ecologically meaningful community reorganisation under degradation pressure.